Environmental Convergence in the Context of Integration between Ukraine and the EU: Empirical Evidence and Policy Implications - Andrii Verstiak; Ruslan Biloskurskyi; Oksana Verstiak; Igor Vinnychuk (Scientific Annals of Economics and Business)
The European Green Deal will play a key role in the development of the environmental policies of the EU and its neighbouring countries (i.e. Ukraine). Accordingly, the implementation of environmental policies will contribute to the development of national economies on a convergent basis of Ukraine and the EU. The aim of this study is to analyse environmental convergence between the EU and Ukraine, taking into account the complex specificities of combining economic growth and reducing environmental impacts. In addition to the classical models of beta, sigma, gamma and delta convergence, we use methods to study environmental convergence that are based on increasing the level of economic development of less developed countries rather than reducing the unevenness of their development and include club convergence and distributional dynamics approaches. Such methodologies emphasise the importance of efforts and policies aimed at bringing countries closer together and creating favourable conditions for them to achieve higher levels of development. The result of the empirical analysis of the environmental convergence of economies using different methodologies shows that the Ecological Footprint is characterised by different results. In this context, a narrowing of the Ecological Footprint gap between countries is shown, indicating common development trends and that countries with lower levels of development are on a faster growth path to catch up with countries with higher levels of development. Another finding is that Russia’s armed invasion has affected Ukraine’s convergence with the EU and will continue to have a negative impact on the country’s economic development and influence on convergence processes.